Respons Pertumbuhan Dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) Varietas Dewata F1 Terhadap Pemberian Berbagai Dosis Pupuk Kandang Sapi Skala Polybag - Dea Ulan Pordayu; Pandu Sumarna; Fadhillah Laila; Yudhi Mahmud; Didi Carsidi (Universitas Wiralodra, 2026)
Fertilization is an important factor in improving the growth and yield of cayenne pepper (Capsicum frutescens L.). Low soil organic matter content and dependence on inorganic fertilizers can reduce soil fertility and productivity. Cattle manure as a source of organic matter has the potential to improve the physical, chemical, and biological properties of the soil and increase the availability of nutrients for plants. This study aimed to determine the effect of various doses of cattle manure on the growth and yield of cayenne pepper (Dewata F1 variety) and to identify the optimal dose. The experiment was conducted in a greenhouse located in Mekargading Village, Sliyeg Subdistrict, Indramayu Regency, at an altitude of 7.5 meters above sea level. The research was carried out during the transition period from the rainy season to the dry season in 2024/2025, from April to July 2025. The research employed an experimental method using a Completely Randomized Design (CRD), consisting of five treatments and five replications. The treatments of cattle manure dosage were: A = control; B = 20 tons/ha; C = 25 tons/ha; D = 30 tons/ha; and E = 35 tons/ha. The results showed that cattle manure significantly affected the growth and yield of cayenne pepper (Dewata F1 variety) under polybag conditions. The best growth and yield were obtained at a dosage of 30 tons/ha, as indicated by improvements in various growth and yield parameters, resulting in highest fruit weight per plant of 700 g/plant.